Um caminho para Troia : estudo de notas manuscritas para aulas e sua contribuição para a composição do ensaio Aspectos estruturais na Ilíada de Donaldo Schüler - Silva, Odi Alexander Rocha da (2017)
This work is dedicated to the study of handwritten notes for classes by Donaldo Schüler. The content of these notes focuses on issues related to the plot of the Iliad, especially those related to Song IX of that work. The interest of this study is to reveal the role that these notes for classes had in the making of the published work of Schüler Aspectos Estruturais na Ilíada. These notes are part of one of the binders, entitled Iliad II, which features handwritten notes for classes on Homer and his works. These notes were made by Schüler when he was a professor at the Federal University of Rio Grande do Sul. From this binder, we chose three pieces as a clipping for analysis. These three pieces belong to the set of discussions corresponding to Song IX of the Iliad. To make easy the reference, the pieces are numbered and classified as follows: Piece 1, which discusses the psychology of the ancient man, Piece 2, which presents a summary of Song IX for didactic purposes and Piece 3, which outlines some reflections on the Phoenix character. The contents of these pieces demonstrate just from their outline the presence of an essayistic thought, marked by questioning, restlessness and reflection. Such thinking, unfolding in more complex reflections such as a thesis and a published essay, reveals through material evidence that, parallel to the classroom, the teacher develops his own essayistic thought, characterized by critical reflections on what he researches and teaches, which is reflected in his scientific production.